Surface circulation in the Gulf of California in summer from surface drifters and satellite images (2004–2006). Issue 7 (12th July 2014) - Lavín, M. F.; Castro, Rubén; Beier, Emilio; Cabrera, Carlos; Godínez, Victor M.; Amador‐Buenrostro, A.
Abstract Surface drifters released in the Gulf of California between June 2004 and August 2006 are used to describe the surface circulation in late spring and summer. In the June to September mean, there was a poleward coastal current on the shelf and slope of the mainland side of the Gulf, with mean speed ∼0.3 m/s; it reached the northern Gulf and joined the cyclonic circulation typical of this zone in summer. In the western half of the southern Gulf, the drifters presented recirculating currents that are due to mesoscale eddies that appear to dominate the surface circulation in summer. In June 2004, the coastal current presented an enhancement event with mean speed around 0.60 m/s and maximum ∼0.80 m/s. It took ∼20 days for a particular drifter to travel the 1000 km from the Gulf entrance to the head. This strengthening of the coastal current was apparent in chlorophyll a and SST satellite images, the drifters following closely the intrusion of warm, chlorophyll‐poor surface water from outside the Gulf. The drifters and the satellite images suggest that the current‐enhancement event lasted less than a month. This mesoscale event was linked with a mesoscale remote forcing in the tropical Pacific coast and with a mesoscale local forcing of the wind. These events seem to occur every year, and are probably important in carrying organisms and properties from the entrance to the whole length of the Gulf.